(untitled) (Research, Society and Development, 2021)
Democratic societies must implement a fair school, understanding as such that one guarantees all young people in training the improvement of their abilities and attributes, as well as the promotion of self-esteem and motivation for learning. This vision goes beyond the supposed equality of opportunity that only takes into account that everyone has access to school, but that perpetuates social inequality. It is necessary that educational systems promote policies that support coexistence, avoiding conflicting attitudes, more or less violent. Conflict is inherent in life and can lead to confrontational situations if there is no effective resolution. One of the goals of the school system is to generate attitudes in students to understand conflict situations and seek solutions to resolve them, based on dialogue and cooperation, capable of ensuring coexistence and eradicating violence from school centers, essential aspects for the school to be fair. The article presents a doctoral research from 2018 in which the oral life history of seventeen male and female professors from Campinas and nine from Catalonia was analyzed. This is a qualitative research based on individual interviews that referred to their attitude towards conflicts in classrooms, how to prevent situations of violence, as well as the exercise of microjustice based on mediation experiences that allow for acquisition of skills to manage conflicts in a positive way and that can materialize in the future the exercise of active citizenship in a democratic society.